Quarante années de recherche - 1970 – 2010 - Abdelfettah BENCHENNA (Tic & Société)
This article aims at proposing a synthesis of the research on ICTs in the southern countries. The authors’ objective is to answer the three following questions: What are the characteristics of this research domain? What are the main key topics emerging from the research on ICTs in the southern countries? what is the importance of criticism posture within the available studies?